2014
DOI: 10.1177/2053019614547741
|View full text |Cite
|
Sign up to set email alerts
|

Human rights and the environment in the Anthropocene

Abstract: Human rights are considered ethical demands that operate at an elevated juridical level. They have become popular legal constructs that contribute to the traditional instrumentalist and the more esoteric functions of law. While there is often considerable criticism leveled against human rights, as creatures of law and as legal mechanisms possessing unique characteristics, they are also uniquely situated and able to perform a singular mediating role in the human–environment interface. The recent mushrooming of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
0
23
0
1
Order By: Relevance
“…Authors, such as Kotzé [43,44,54], Bosselmann [5,9] and Bodansky [53], have investigated whether or not we already have an "international environmental constitution". The answer seems to be "no", international environmental law appears to constitute merely the commitments by states, rather than a constitutional order [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors, such as Kotzé [43,44,54], Bosselmann [5,9] and Bodansky [53], have investigated whether or not we already have an "international environmental constitution". The answer seems to be "no", international environmental law appears to constitute merely the commitments by states, rather than a constitutional order [50].…”
Section: Discussionmentioning
confidence: 99%
“…In any case, some might say the rule of law is an "anthropocentric ideal" [44] because its ultimate aim is the protection of the rights of humans. This means that per definition the rule of law may be little concerned about, or has no relevance for, nature as a subject of legal rules.…”
Section: Implementation Of "Wild Law" Through Environmental Constitutmentioning
confidence: 99%
“…In making this finding, the court gave credence to the argument that ecologically SD demands restriction of 'social-economical activities that obstruct natural cycles, structures and functions while promoting ecological resilience'. 73 It affirmed that survival of human beings depends not only on the availability of clean water as an isolated public good but on the factors upon which their well-being depends. Given that all life depends on well-functioning hydrological systems, this reasoning has shown that the ecocentrism contemplated under the principle of SD is not necessarily misanthropic because it benefits human beings who depend on different natural systems and biological process for survival.…”
Section: Exploring the Interlinkagesmentioning
confidence: 99%
“…see Ceballos et al, 2015;Ripple et al, 2017;Watts, 2018). Humans tend to focus on their own needs while ignoring, diminishing or denigrating the needs of other species and natural systems (Hajjar Leib, 2011;Kotzé, 2014). The anthropocentric culture has manifested itself strongly also in design.…”
Section: Introductionmentioning
confidence: 99%